The transition from 3C SiC (1 1 1) to graphene captured by Ultra High Vacuum Scanning Tunneling Microscopy. (September 2015) - Gupta, B.; Placidi, E.; Hogan, C.; Mishra, N.; Iacopi, F.; Motta, N.
Abstract: In this paper we clarify the transformation mechanism of 3C-SiC into graphene upon thermal decomposition, by a combination of high resolution Scanning Tunneling Microscopy (STM) images and first principle calculations. We studied the transition from 3C-SiC to graphene by high temperature annealing of C-terminated 3C SiC (1 1 1)/Si (1 1 1) samples in Ultra High Vacuum. By using STM we were able to observe very clear atomic resolution images of the transition from SiC ( √ 3 × √ 3 ) R 30 ° to a new intermediate stage SiC 3 2 × √ 3 R 30 ° (very close to the graphene (2 × 2) reconstruction) after annealing at 1250 °C. We also obtained images of the transformation of the intermediate structure into a (1 × 1) monolayer graphene, caused by further sublimation of atoms in the subsurface layer. We have interpreted the results by using Density Functional Theory – Local Density Approximation calculations, which give full account of the SiC ( √ 3 × √ 3 ) R 30 ° reconstruction, but fail to describe the SiC 3 2 × √ 3 R 30 ° structure due to its incommensurability with the 3C-SiC (1 1 1) lattice.